Stabilizing Unstable Periodic Orbits of the Multi-Scroll Chua's Attractor - Boukabou, A.; Chebbah, A.; Belmahboul, A. (Nonlinear Analysis: Modelling and Control, 2007)
This paper addresses the control of the n-scroll Chua’s circuit. It will be shown how chaotic systems with multiple unstable periodic orbits (UPOs) detected in the Poincar´e section can be stabilized as well as taking the system dynamics from one UPO to another.
Keywords: chaos; Chua’s circuit; multi-scroll chaotic attractor; nonlinear control